Case report: A STAT1 gain-of-function mutation causes a syndrome of combined immunodeficiency, autoimmunity and pure red cell aplasia - Xie, Yifan; Shao, Fenli; Lei, Juan; Huang, Na; Fan, Zhidan; Yu, Haiguo (Frontiers in Immunology, 2022)
Inherited autosomal dominant gain-of-function (GOF) mutations of signal transducer and activator of transcription 1 (STAT1) cause a wide range of symptoms affecting multiple systems, including chronic mucocutaneous candidiasis (CMC), infections, and autoimmune disorders. We describe a rare case of STAT1 mutation with recurrent CMC, lung infections, and anemia. According to the whole-exome sequencing (WES), the patient was genetically mutated in STAT1 GOF (c.854A>G, p.Q285R), and bone marrow biopsy suggested pure red cell aplasia (PRCA). As a functional verification, STAT1 levels and phosphorylation (p-STAT1) of peripheral blood mononuclear cells (PBMCs) following IFN-γ stimulation in STAT1 GOF patient was higher than in the healthy control. Combination therapy of blood transfusion, antimicrobials, intravenous immunoglobulin, methylprednisolone, and the Janus Kinase (JAK) specific inhibitor ruxolitinib was used during treatment of patients. The patient also received a hematopoietic stem cell transplant (HSCT) to help with infections and anemia. This is the first reported case of STAT1 GOF disease complicated with PRCA. This complication might be attributed to immune disorders caused by STAT1 GOF. Furthermore, ruxolitinib may be a viable therapeutic option before HSCT to improve disease management.